Penerapan PENERAPAN MODEL PEMBELAJARAN KOLABORATIF MENGGUNAKAN MEDIA PAPAN BACA UNTUK MENINGKATKAN MINAT MEMBACA SISWA KELAS 1 MATA PELAJARAN BAHASA INDONESIA DI SDN POHSANGIT KIDUL 1 - Dandi Ferdiansyah; Didit Yulian Kasdriyanto; Shofia Hattarina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the implementation and effectiveness of collaborative learning models using reading board media to improve reading interest of grade 1 students in Indonesian language subjects. The goal is to create interesting and enjoyable learning and achieve the goals that have been set.This study uses the Classroom Action Research (PTK) method with 28 first-grade students as research subjects. Efforts to increase reading interest are carried out through the implementation of collaborative learning using reading board media. The results of this study showed significant changes in student learning. The implementation of learning using a collaborative learning model using reading board media in class 1 with 28 students was carried out with 2 cycles. Based on the results of cycle I, 12 out of 28 students had an average below 70% so that the average learning outcomes of class 1 students were 69.82% in cycle I. The average increased in cycle II, which was 78.21% where these results had reached the student's learning completion value. In terms of increasing students' interest in reading, the percentage increase in cycle I in the first meeting was 50.8% then in cycle II it increased to 72.1%. The results show that the implementation of a collaborative learning model using reading board media can increase students' interest in reading.